Promoting knowledge economy, human capital, and dual careers of athletes: a critical approach to the Global Sports Talent Development Project in South Korea. Issue 4 (2nd October 2019) - Nam, B. H.; Shin, Y. H.; Jung, K. S.; Kim, J.; Nam, S.
ABSTRACT: This study explores four core vocational development programmes for former Korean elite athletes that were designed to develop their linguistic and cross-cultural competencies and professional knowledge in sport. Further, this study seeks to determine if there are any positive influences and existing challenges with regard to fostering potential sports human capital on the global stage. Qualitative individual interviews were conducted with 19 participants, who were divided into two groups. The first group of participants included four male senior administrators who have interacted with former elite athletes who participated in vocational training programmes. The second group of participants included 15 retired elite athletes who participated in vocational development programmes with governmental non-profit sports organizations. All interviewees shared their own experiences and perceptions of how the programming created opportunities for those who were academically disadvantaged to enable them to improve their chances in obtaining occupations in sports administration. However, social justice concerns still emerged from the elite sporting system. Whereas the core programming assisted former athletes in overcoming various life challenges through education, there are still limited full-time employment opportunities in sports administration at the national level. This study critically analyses the emerging structural problems in Korea's elite sporting system and suggests plausible strategies to create more educational opportunities. In this regard, this study considers ways to promote the knowledge economy and sports human capital through the lens of the dual careers of athletes.